Treatment of Winery Wastewater by Anodic Oxidation Using Bdd Electrode - Salazar-Gonzalez, R; Garcia-Mena, V (Elsevier Ltd, 2018)
The effective removal of organics from winery wastewater was obtained in real residual effluents from the wine industry using anodic oxidation (AO). The effluent had an initial organic load of [COD]0 of 3490 mg L−1 equal to [TOC]0 of 1320 mg L−1. In addition, more than 40 organic compounds were identified by means of GC-MS. Different density currents as well as the addition of electrolytes were tested during electrolysis. The results show the decay of [COD]t by 63.6% when no support electrolyte was added, whereas almost total mineralization and disinfection was reached after adding of 50 mM of sodium sulfate and sodium chloride and applying higher density currents. The presence of sulfate and chloride in large concentration favors the production of oxidants such as hydroxyl radicals and active chlorine species that react with organics in solution. Moreover, the addition of a supporting electrolyte to industrial wastewater increases conductivity, reduces cell potential and therefore, decreases the energy consumption of the AO process. © 2018 Elsevier Ltd